2019
DOI: 10.1002/ajmg.b.32760
|View full text |Cite
|
Sign up to set email alerts
|

AHRR methylation predicts smoking status and smoking intensity in both saliva and blood DNA

Abstract: Many existing DNA repositories do not have robust characterizations of smoking, while for many currently ongoing studies, the advent of vaping has rendered traditional cotinine‐based methods of determining smoking status unreliable. Previously, we have shown that methylation status at cg05575921 in whole blood DNA can reliably predict cigarette consumption. However, whether methylation status in saliva can be used similarly has yet to be established. Herein, we use DNA from 418 biochemically confirmed smokers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 41 publications
6
67
4
Order By: Relevance
“…Still, the actual consumption of cigarettes that these cotinine levels represent may be lower. In our studies of adults who only smoked cigarettes that used this same ELISA assay, the same methylation level corresponded to~2 cigarettes per day [15]. Furthermore, the majority of the 19 W3 subjects, whose data is given in Fig.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Still, the actual consumption of cigarettes that these cotinine levels represent may be lower. In our studies of adults who only smoked cigarettes that used this same ELISA assay, the same methylation level corresponded to~2 cigarettes per day [15]. Furthermore, the majority of the 19 W3 subjects, whose data is given in Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Dozens of genome wide studies have suggested that DNA methylation approaches may address some of these limitations [13,14]. Building on these studies, we and others have shown that single assessments of blood or saliva DNA methylation status at cg05575921, a CpG residue in the aryl hydrocarbon repressor receptor (AHRR) locus, is extremely sensitive to regular adult smoking [15,16]. Furthermore, in preliminary work, we have shown that saliva DNA assessment of cg05575921 predicts adolescent smoking status [17].…”
Section: Introductionmentioning
confidence: 83%
“…Although DNA methylation loci associated with numerous exposures have been identified, most have not been demonstrated to be able to act as markers. The exceptions, CpG markers for current smoking and current heavy alcohol intake, were identified in cohorts that used questionnaires that assessed detailed current and previous use, including type, quantity, frequency, and duration of use, age when first started using, and age when quitting (if applicable) [37,40,59,60]. Identification of epigenetic markers for additional personal exposures that may be associated with breast cancer risk would also require a robust characterization of the exposure and data analysis for potential associations with the peripheral blood epigenome.…”
Section: Proposed Approaches and Expected Resultsmentioning
confidence: 99%
“…These findings suggest that epigenetic signatures can represent a biological memory of past exposures and that such signatures may be retained in the exposed stem and progenitor cells [29]. More recently, AHRR hypomethylation in saliva was also shown to predict smoking with an AUC of 0.971 [40]. Thus, salivary DNA methylation may also serve as biomarkers of environmental exposures.…”
Section: Dna Methylation As Molecular Markers Of Environmental Exposuresmentioning
confidence: 86%
“…In addition to being a predictor of smoking habits [52], AHRR cg05575921 methylation from whole blood or saliva DNA is a validated predictor of smokingrelated morbidity and mortality [35,49]. For instance, AHRR cg05575921 hypomethylation has been associated with enhanced carcinogenesis especially in the lungs [10,31,35,38].…”
Section: Discussionmentioning
confidence: 99%